2016
DOI: 10.1155/2016/4987436
|View full text |Cite
|
Sign up to set email alerts
|

How to Achieve High-Quality Oocytes? The Key Role of Myo-Inositol and Melatonin

Abstract: Assisted reproductive technologies (ART) have experienced growing interest from infertile patients seeking to become pregnant. The quality of oocytes plays a pivotal role in determining ART outcomes. Although many authors have studied how supplementation therapy may affect this important parameter for both in vivo and in vitro models, data are not yet robust enough to support firm conclusions. Regarding this last point, in this review our objective has been to evaluate the state of the art regarding supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…16 Some have advocated that the supply of certain antioxidants does improve outcomes in ART. 17,18 However, several studies have obtained results similar to our study. Although antioxidants involve a significant improvement in embryonic 2 Clinical Medicine Insights: Therapeutics quality, the remaining parameters tested are not statistically superior.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…16 Some have advocated that the supply of certain antioxidants does improve outcomes in ART. 17,18 However, several studies have obtained results similar to our study. Although antioxidants involve a significant improvement in embryonic 2 Clinical Medicine Insights: Therapeutics quality, the remaining parameters tested are not statistically superior.…”
Section: Introductionsupporting
confidence: 90%
“…In addition, inositols have a sensitizing effect on insulin. 18 It is thought that inositol plays a critical role in oocyte maturation and embryonic development. Previous studies have shown that oral supplements with inositol can reduce oxidative stress and improve stimulation protocols and pregnancy outcomes in nonfertile women with poor-quality oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Different from the MPTP, UCPs can be actively regulated by many factors based on the status of the mitochondria. Activation of UCPs usually has beneficial effects on mitochondrial functions including balancing the Δψ, accelerating electron transport and finally reducing ROS formation and cellular oxidative damage [168,169]. Melatonin increases the activity of UCPs either by upregulating gene expression or directly acting on these proteins [57,58,60].…”
Section: Melatonin: a Potent Protector Of Mitochondriamentioning
confidence: 99%
“…Reflecting these elements on the clinical management, we recently showed MI beneficial effects on semen parameters before in vitro fertilization [4] and that both the isoforms of inositol and combined therapy were effective in improving ovarian function and metabolism in patients with PCOS, although MI showed the most marked effect on the metabolic profile, whereas DCI reduced hyperandrogenism better [2]. Although Unfer et al [1] proposed MI:DCI ratio of 40:1 as the most appropriate, we solicit further studies to establish the best therapeutic strategies based on patient's clinical condition, also in combination with other nutraceuticals [5].…”
Section: Letter To the Editormentioning
confidence: 86%